Composites with Koch fractal activated carbon fiber felt screens for strong microwave absorption. (15th November 2016) - Xia, Shaoxu; Yao, Bin; Chen, Qiping; Yu, Xinhai; Wu, Qilin
Abstract: This work presents a strong microwave absorber with Koch fractal activated carbon fiber (ACF) felt screens. The effects of arrangements (spacing d) and structure parameters (iteration number n, initial side-length L) of Koch fractal units on the microwave absorption (MA) properties were investigated. It was observed that the optimal spacing d was obtained at 20 mm, and the reflection loss (RL) decreased in the low frequency-range from 6 to 9 GHz, but increased in the high-frequency range from 16 to 18 GHz apparently with increasing n and L. The strongest MA could reach – 62.8 dB. The relationship between ACF area ratio and RL was described.